Population Dynamics of the Sting Nematode in California Turfgrass - Bekal, Sadia (Plant disease, 2000)
Population densities of Belonolaimus longicaudatus were monitored at monthly intervals at the Tamarisk country club golf course (1993 to 1994) and at the Annenburg Estates and Desert Island golf courses (1998). All three courses are located at Rancho Mirage, Coachella Valley, CA. The bermuda grass in the sampling area typically exhibited chlorosis at the beginning of April when the sting nematode populations began to increase. At the Tamarisk golf course, population density peaked in October, with 1,000 nematodes per 100 cm3 of soil, but declined rapidly, with the lowest population density occurring in December with approximately 50 nematodes per 100 cm3 of soil. At the Annenburg Estates and Desert Island golf courses, the nematode population densities peaked in June and July but declined rapidly to less than half of that density, presumably because of B. longicaudatus-caused host decline. Soil temperature and fluctuation of nematode densities were significantly correlated at all locations. Nematode distribution was greatest in the top 15 cm of soil except during the hottest summer months, when the population was higher at depths of 15 to 30 cm